An American Board of Surgery Pilot of Video Assessment of Surgeon Technical Performance in Surgery. Issue 4 (16th April 2023) - Pryor, Aurora D.; Lendvay, Thomas; Jones, Andrew; Ibáñez, Beatriz; Pugh, Carla
Abstract : Objective: The American Board of Surgery (ABS) sought to investigate the suitability of video-based assessment (VBA) as an adjunct to certification for assessing technical skills. Background: Board certification is based on the successful completion of a residency program coupled with knowledge and reasoning assessments. VBA is a new modality for evaluating operative skills that have been shown to correlate with patient outcomes after surgery. Methods: Diplomates of the ABS were initially assessed for background knowledge and interest in VBA. Surgeons were then solicited to participate in the pilot. Three commercially available VBA platforms were identified and used for the pilot assessment. All participants served as reviewers and reviewees for videos. After the interaction, participants were surveyed regarding their experiences and recommendations to the ABS. Results: To the initial survey, 4853/25, 715 diplomates responded. The majority were neither familiar with VBA, nor the tools used for operative assessments. Two hundred seventy-four surgeons actively engaged in the subsequent pilot. One hundred sixty-nine surgeons completed the postpilot survey. Most participants found the process straightforward. Of the participants, 74% felt that the feedback would help their surgical practice. The majority (81%) remain interested in VBA for continuing medical education credits. Using VBA in continuous certification could improve surgeon skills felt by 70%. Two-thirds of participants felt VBA could help identify and remediate underperforming surgeons. Identified barriers to VBA included limitations for open surgery, privacy issues, and technical concerns. Conclusions: VBA is promising as an adjunct to the current board certification process and should be further considered by the ABS.